Elaboração da matriz origem destino do transporte público coletivo por ônibus da cidade de Palmas-TO com a utilização dos dados dos sistemas inteligentes de transporte - Monteiro, Ana Jéssica Freire (Universidade Federal do Tocantins, 2021)
To understand the travel behavior of users of public transport, the Origin-Destination Matrix (O/D) are elaborated, based on data collected, traditionally, manually and in the field, as in household surveys. These surveys are commonly time-consuming and costly, usually carried out every 10 years. However, in recent years, researchers have been using the data generated in the technologies present in the transport system for the elaboration of O/D Matrix, a more efficient, precise and less costly way, which allows the identification of the points of embarkation and disembarkation of the users. Among the technologies used are the Automated Fare Collection (AFC) and the Bus Monitoring System (SMB). Given these advantages and because Palmas, the place of study, have AFC technologies on their buses, for validating payment and time recording of trips made by each passenger, and SMB for spatial records through vehicle tracking, this work uses a methodology similar to that presented in the Technical, Economic and Environmental Feasibility Study of BRT Palmas (EVTEA - BRT Palmas), for the elaboration of the O/D Matrix. However, advances are made when using python programming for one of the most important stages of the work, which is the linking of AFC and SMB data, making it possible to define the location of passengers' embarkations and disembarkations. The applied methodology allowed the inference for 63% of the electronic card registrations, which served as a basis for inference of the other displacements. The results were compared with those of EVTEA BRT Palmas, which had been validated based on data collected in the field, showing satisfactory results and which represented the flow of passengers on the city's public transport.